Severity of frailty using modified Thai frailty index, social factors, and prediction of mortality among community-dwelling older adults in a middle-income country - Morkphrom, Ekkaphop; Srinonprasert, Varalak; Sura-amonrattana, Unchana; Siriussawakul, Arunotai; Sainimnuan, Supawadee; Preedachitkun, Rinrada; Aekplakorn, Wichai (Frontiers in Medicine, 2022)
Background: Frailty has increasingly recognized as a public health problem for aging populations with significant social impact, particularly in low and middle-income countries. We aimed to develop a modified version of the Thai Frailty Index (TFI) and explore the association between different frailty status, socioeconomic factor and mortality in community-dwelling older people from a middle-income country. Methods: The data from participants aged ≥ 60 years in the Fourth Thai National Health Examination Survey were used to construct the 30-itemed TFI. Cut-off points were created based on stratum-specific likelihood ratio. TFI ≤ 0.10 was categorized as fit; 0.10-0.25 as prefrail; 0.25-0.45 as mildly frail, and > 0.45 as severely frail. The association of frailty status with mortality was examined using Cox proportional hazard models. Findings. Among 8,195 older adults with mean age of 69.2 years, 1,284 died during the 7-year follow up. The prevalence of frailty was 16.6%. The adjusted hazard ratio (aHR) for mortality in prefrail was 1.76 (95%CI=1.50-2.07), mildly frail 2.79 (95%CI = 2.33-3.35), and severely frail 6.34 (95%CI = 4.60-8.73). Having a caretaker in the same household substantially alleviated mortality risk for severely frail men with aHR 3.24 (95%CI =1.82 – 5.76) compared to aHR 18.78 (95%CI = 8.13-43.33) among those living without caretaker. Interpretation: The severity of frailty classified by the modified TFI can predict long-term mortality risk for community dwelling older adults. Identification of severely frail older people to provide appropriate care might alleviate mortality risk. Our findings can inform policymaker to appropriately allocate services in resource-limited setting